2009
DOI: 10.1021/ja904042h
|View full text |Cite
|
Sign up to set email alerts
|

HexacationicDendriphosLigands in the Pd-Catalyzed Suzuki−Miyaura Cross-Coupling Reaction: Scope and Mechanistic Studies

Abstract: The combination of Pd(2)dba(3) x CHCl(3) and hexacationic triarylphosphine-based Dendriphos ligands (1-3) leads to a highly active catalytic system in the Suzuki-Miyaura cross-coupling reaction. Under relatively mild reaction conditions, nonactivated aryl bromides and activated aryl chlorides can be coupled at a low Pd loading (0.1 mol %). The observed activity of this catalytic system, in particular in coupling reactions of aryl chlorides, is dramatically higher than that of conventional Pd catalysts employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 128 publications
0
71
1
Order By: Relevance
“…[16] Bulky, dendritic triarylphosphanes that display high efficiency in Suzuki cross-coupling were also reported, but the latter may all potentially behave as hemilabile ligands so that their efficiency possibly relies on secondary ligating groups. [17,18] Note that the coordination chemistry of calixarenyl monophosphanes related to those described in this paper has recently been studied thoroughly. A striking feature of these ligands concerns their ability to behave as supramolecular chelators towards metal-arene moieties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Bulky, dendritic triarylphosphanes that display high efficiency in Suzuki cross-coupling were also reported, but the latter may all potentially behave as hemilabile ligands so that their efficiency possibly relies on secondary ligating groups. [17,18] Note that the coordination chemistry of calixarenyl monophosphanes related to those described in this paper has recently been studied thoroughly. A striking feature of these ligands concerns their ability to behave as supramolecular chelators towards metal-arene moieties.…”
mentioning
confidence: 99%
“…No significant change in activities were observed, suggesting that no palladium nanoparticles were present. [18] Suzuki-Miyaura cross-coupling at room temperature: The monophosphanes were further assessed for use in reactions that were carried out at room temperature. These runs were performed with an ArBr/Pd ratio of 1000 (0.1 mol %).…”
mentioning
confidence: 99%
“…On the other hand, by employing the dendritic 2Gn[CO 2 K]-palladium complex as a catalyst (n=1, 2), the cross-coupling products 12 were obtained in fair chemical yields in both cases (G1: 61%, G2: 55%; Table 2, entries 2, 3). 49) However, a positive dendritic effect on chemical yields, 19,27,29,30,[50][51][52][53][54][55] which would mean that the reactivity was enhanced via an increase in the generation number of the dendrimers, has not been observed.…”
Section: 48)mentioning
confidence: 99%
“…The combination of these ligands with a suitable metal precursor leads to in situ formation of homogeneous catalysts that have found applications in Pd-catalyzed Suzuki-Miyaura reactions as well as in Rh-catalyzed hydroformylation reactions. [49,55,61,62] The electronic properties of all oligocationic ligands in the series have been evaluated through the 1 J P,Se coupling constant of the corresponding phosphine selenides ( Table 2, entries 5-15). [49] Furthermore, for 8 a and 11, the corresponding complexes trans-[RhCl(CO)L 2 ] (L= 8 a, 11) have been synthesized and characterized in terms of the CO stretching frequency (Table 2, entries 28 and 29).…”
Section: Steric and Electronic Properties Of Ionic Phosphine Ligandsmentioning
confidence: 99%
“…A remarkable enhancement of activity, both in terms of reaction rate as well as in terms of substrate scope, was observed upon the use of 8 b compared to TPP (Table 3, entry 6). [61,62] In further studies, a systematic comparison of the catalytic properties of hexacationic 8 b to those of neutral triarylphosphine ligands that match either the steric or the electronic properties of 8 b, as well as ligands that contain only four (9 b) or two (10 b) cationic groups, was carried out. From these investigations it was concluded that the Coulombic interA C H T U N G T R E N N U N G liA C H T U N G T R E N N U N G gand repulsion that originates from these presence of as much as six permanently charged groups in the ligand structure of 8 b leads to the observed increased activity, rather than the enlarged cone angle or the reduced s-donating strength of 8 b.…”
Section: A C H T U N G T R E N N U N G (Tppts) 3 ]mentioning
confidence: 99%